2015
DOI: 10.1075/eww.36.1.02nel
|View full text |Cite
|
Sign up to set email alerts
|

Response to Davies and Fuchs

Abstract: Commentary to: Davies, Mark, and Robert Fuchs. 2015. "Expanding horizons in the study of World Englishes with the 1.9 billion word Global Web-based English Corpus (GloWbE)". English World-Wide 36:1–28 (This issue). DOI:10.1075/eww.36.1.01dav

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 3 publications
1
16
0
Order By: Relevance
“…For this reason, it has been suggested that one million words may be a sufficiently large sample for this kind of study. Clearly, this does not imply that the larger size of GloWbE is not a very valuable feature, and that other types of collocational studies cannot profit from it (Nelson : 38). However, the finding here does confirm previous studies, such as Nurmi () and Hundt and Leech (), which show that larger does not necessarily mean better.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, it has been suggested that one million words may be a sufficiently large sample for this kind of study. Clearly, this does not imply that the larger size of GloWbE is not a very valuable feature, and that other types of collocational studies cannot profit from it (Nelson : 38). However, the finding here does confirm previous studies, such as Nurmi () and Hundt and Leech (), which show that larger does not necessarily mean better.…”
Section: Resultsmentioning
confidence: 99%
“…The study of collocations is generally said to be highly sensitive to corpus size. More specifically, the ICE corpus, which was born as a tool for grammatical analysis, is considered to be of limited value for phraseological and collocational studies (Nelson : 38). Therefore, we might expect that ICE and GloWbE will offer quantitatively different results for the collocations of these modals.…”
Section: Modals Of Necessity: Collocations and Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps the most major change of contents for second generation corpora is the recommendation for the inclusion of a new component of electronic texts, totalling up to 500,000 words, making the total maximum size of a second generation corpus 1.5 million words. Indeed, from her thorough comprehensive comparison between ICE and the GloWbE corpus of blogs and websites (Davies, ), Loureiro‐Porto (, p. 468) concludes that ‘the future of ICE should include web registers alongside the text types included so far’; from other comparisons, similar conclusions are drawn by Mair (), Mukherjee (), Nelson () and Peters (), in their responses to Davies and Fuchs (). A list of possible electronic texts is presented in Appendix 3 for discussion.…”
Section: Second Generation Corporamentioning
confidence: 79%
“…Of course, English as used on the Internet is becoming increasingly important and influential, so we must welcome the GloWbE corpus as a means of examining its characteristics. We should not, however, rush to the conclusion that bigger is necessarily better in all areas of linguistic enquiry (Nelson ).…”
mentioning
confidence: 97%